Microalbuminuria : - Winocour, Peter H. (Cambridge University Press, 1998)
'This textbook will be essential reading for doctors interested in microalbuminuria and its significance in diabetes and hypertension, and as a non-specific marker of disease. All topics are comprehensively covered and include extensive up to date references. Every effort has been made to ensure that this book is as contemporary as possible, with numerous notes being added during the proof-reading. In summary, this is an informative, well-written book that will be of great interest to diabetetologists